PHÂN BỐ TỔNG CARBON HỮU CƠ (TOC), TỔNG NITƠ (TN), TỶ SỐ TOC/TN VÀ GIÁ TRỊ ĐỒNG VỊ BỀN CARBON (δ13C) CỦA VẬT CHẤT HỮU CƠ TRONG TRẦM TÍCH - Quy, Trần Đăng; Tuệ, Nguyễn Tài (Vietnam Journal of Earth Sciences, 2012)
Spatial distribution of total organic carbon (TOC), total nitrogen (TN), TOC/TN ratio, and stable carbon isotopes value (δ13C) in surface sediments of Tien Yen Bay, northeast Vietnam Tien Yen Bay (northeast Quang Ninh province) is one of the most important mangrove ecosystem sites in Vietnam. This study was aimed to access the role of mangrove forests in supplying organic matters to the coastal zone. The results showed that the concentrations of TOC and TN were relatively low. TOC, TN, and fine grained sediments (<0,063 mm) were highly concentrated in the center of the bay, controlled by topography characteristics. The results of TOC/TN ratio and δ13C value methods indicated that mangrove forests play an important role on suppling organic matters to other ecosystems in Tien Yen Bay. There was a decrease trend of organic matters from near shore area to the center of the bay. These matters orginated from mangrove forests; however, those from Cai Bau - Vinh Thuc islands to offshore area mainly came from phytoplankton. The results also highlighted an important role of mangrove forests in the conservation of ecosystems in the study area.